A case of primary biliary cirrhosis in a patient with rheumatoid arthritis. Issue 1 (1st December 2015) - Bekki, Norifumi; Bae, Sung Kwan; Yoshizawa, Seiji; Shiota, Ayaka; Gushima, Toshifumi; Motoshita, Junichi; Shimoda, Shinji; Aiba, Yoshihiro; Komori, Atsumasa; Nakamura, Minoru; Takahashi, Kazuhiro
Key Clinical Message: The true prevalence of PBC in RA is not well known. Herein, we report an unusual case of a patient with PBC and RA, and discuss the association between these two diseases. PBC should be ruled out in the differential diagnosis of patients with RA having abnormal liver function tests. Abstract : The true prevalence of PBC in RA is not well known. Herein, we report an unusual case of a patient with PBC and RA, and discuss the association between these two diseases. PBC should be ruled out in the differential diagnosis of patients with RA having abnormal liver function tests.